Retinoids as Alternative Antifungal Agents Against Candida albicans: In Vitro and In Silico Evidence - Terenzio Cosio; Alice Romeo; Enrico Salvatore Pistoia; Francesca Pica; Claudia Freni; Federico Iacovelli; Augusto Orlandi; Mattia Falconi; Elena Campione; Roberta Gaziano (Microorganisms)
Candida albicans (C. albicans) is the most common pathogen responsible for a wide spectrum of human infections ranging from superficial mucocutaneous mycoses to systemic life-threatening diseases. Its main virulence factors are the morphological transition between yeast and hyphal forms and the ability to produce biofilm. Novel antifungal strategies are required given the severity of systemic candidiasis, especially in immunocompromised patients, and the lack of effective anti-biofilm treatments. We previously demonstrated that all-trans retinoic acid (ATRA), an active metabolite of vitamin A, exerted an inhibitory effect on Candida growth, yeast–hyphal transition and biofilm formation. Here, we further investigated the possible anti-Candida potential of trifarotene and tazarotene, which are the other two molecules belonging to the retinoid family, compared to ATRA. The results indicate that both drugs were able to suppress Candida growth, germination and biofilm production, although trifarotene was proven to be more effective than tazarotene, showing effectiveness comparable to ATRA. In silico studies suggest that all three retinoids may exert antifungal activity through their molecular interactions with the heat shock protein (Hsp) 90 and 14α-demethylase of C. albicans. Moreover, interactions between retinoids and ergosterol have been observed, suggesting that those compounds have great potential against C. albicans infections.